High Prevalence of Mycotoxigenic Fungi and Aflatoxin B1 Contamination in Corn and Wheat Grains Grown to Albania: Implications for Food Safety - L. Mato; Z. Damani; J. Spahiu; E. Halimi; B. Seiti; D. Topi (Journal of Food Quality and Hazards Control, 2024)
Background: Today, mycotoxins are considered critical contaminants in foodstuffs produced by fungi, highlighting the importance of food safety to human health. The toxigenic fungi invasion and mycotoxin production are highly variable and depend on climate, plant, and agronomic practices. Among these, Aflatoxins (AFs) are considered the most potent toxins. This study investigated the fungi presence and AFB1 contamination in corn and wheat grown in Albania during the 2022 harvesting year. Methods: Wheat samples were collected during the summer, while corn during the autumn, and further analyzed. Mycological contamination assessment applied the Verband Deutscher Landëirtschaftlicher Untersuchungs ̶ und Forschungsanstalten (VDLUFA) procedures. The AFB1 levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method. The MATLAB R2016b software was applied to perform statistical analysis. The Estimated Daily Intake on AFB1 was calculated to evaluate human exposure. Results: The genera Alternaria, Aspergillus, Cladosporium, Fusarium, and Penicillium were isolated, with higher rates of contamination in corn and the highest frequency Penicillium genus (77.89%). The Korça region presented a higher fungal load, 104 Colony Forming Unit (CFU)/g in corn. The AFB1 incidence (88.23%) in corn, was significantly higher than in wheat (4.91%). Additionally, the maximum level in corn was found 69.120 μg/kg, while in wheat, only 0.402 μg/kg. None of the wheat samples, in contrast to the 41.18% of corn samples, exceeded the threshold when referring to the respective Maximum Residue Levels. Conclusions: Our observation indicates a higher rate of AFB1 contamination in corn than in wheat. The high concentration levels and contamination incidence in corn require targeted interventions to reduce the AFB1 amounts. Strengthened regulation based on scientific evidence can reduce contamination outbreaks, economic implications, and potential benefits, such as increased consumer trust. Our study indicates that the exposure to AFB1 originates from corn consumption among the adult population.